Media Interaktif Pembelajaran Kandungan Gizi Dalam Sayuran Serta Manfaat Dalam Tubuh Manusia - Christian Aditia; Liliana Liliana; Gregorius Satia Budhi (Jurnal Infra, 2016)
The vegetable is an excellent food for the human body, many various of vegetables that sold at market make vegetable contain many different contents and benefits, many societies understand about vegetable but many less understood what the side effects of certain vegetables. Nowadays, there are many applications spread out there, but they could not get society’s concern because lack of image dan voice for naration.This application will give you knowledge about the content and the benefits, side effects, and processing interactively and it has images, sound, music, and interesting simulation, so that users could directly involved in the learning process. The material in this interactive media taken from 13 kinds of vegetables which are described the content and benefits, side effects, and processing. For content and material benefits, and side effects are provided animationfor material processing in the form of simulation. There is also a test to measure the users understanding towards material that already studied. This application was created using Adobe Flash CS6.With the simulation and animation that is contained in this application can really help users to understand the material being studied. Based on survey’s result from 30 respondents, 70% respondents agreed the explication from the material, 72.5% agreed that images support in learning process and 80% agreed that animation support in learning process. Thus will increase interest in learning from user applications.